Influence of solubilization and AD-mutations on stability and structure of human presenilins. Issue 1 (December 2017) - Yang, Ge; Yu, Kun; Kaitatzi, Christina-Symina; Singh, Abhilasha; Labahn, Jörg
Abstract Presenilin (PS1 or PS2) functions as the catalytic subunit of γ-secretase, which produces the toxic amyloid beta peptides in Alzheimer's disease (AD). The dependence of folding and structural stability of PSs on the lipophilic environment and mutation were investigated by far UV CD spectroscopy. The secondary structure content and stability of PS2 depended on the lipophilic environment. PS2 undergoes a temperature-dependent structural transition from α-helical to β-structure at 331 K. The restructured protein formed structures which tested positive in spectroscopic amyloid fibrils assays. The AD mutant PS1L266F, PS1L424V and PS1ΔE9 displayed reduced stability which supports a proposed 'loss of function' mechanism of AD based on protein instability. The exon 9 coded sequence in the inhibitory loop of the zymogen was found to be required for the modulation of the thermal stability of PS1 by the lipophilic environment.